Serologic Evaluation of Healthcare Workers Caring for COVID-19 Patients in the Republic of Korea - Ko, Jae-Hoon; Lee, Ji Yeon; Kim, Hyun Ah; Kang, Seung-Ji; Baek, Jin Yang; Park, Su-Jin; Hyun, Miri; Jo, Ik Joon; Chung, Chi Ryang; Kim, Yae-Jean; Kang, Eun-Suk; Choi, Young Ki; et al. (Frontiers in Microbiology, 2020)
Safety of healthcare workers (HCWs) against SARS-CoV-2 transmission is an important aspect of managing the COVID-19 pandemic. In the Republic of Korea, highly stringent infection prevention and control (IPC) guidelines are implemented, and reports of healthcare-associated SARS-CoV-2-transmission among HCWs are limited. However, subclinical infections may have been missed by the current symptom-based screening strategy. To evaluate the risk of undetected SARS-CoV-2 transmissions from COVID-19 patients to HCWs, we conducted a multi-center seroprevalence study after the first surge of the COVID-19 outbreak. A total of 432 HCWs was evaluated, comprising 309 HCWs designated to laboratory-confirmed COVID-19 patient care and 123 non-designated HCWs. Designated HCWs wore personal protective equipment including an N95 respirator, eye protection, hooded overalls, shoe covers, and inner and outer gloves. Use of a powered air-purifying respirator was recommended for aerosol-generating procedures or long-duration care activities. A high sensitivity (99.1%) fluorescence immunoassay IgG kit was used as the initial screening test, and two enzyme-linked immunosorbent assay kits for total and IgG antibodies were used to confirm the test results. A microneutralization test was additionally performed to evaluate the neutralizing activity of positive specimens. Among the evaluated HCWs, none of the non-designated HCWs had a positive result, while one of the HCWs designated for COVID-19 patient care (1/309, 0.3%) was seropositive for SARS-CoV-2 with confirmed neutralizing activity (1:40). This finding suggests that subclinical seroconversion may occur among HCWs caring for COVID-19 patients, although the risk is low under strict IPC guidance.